Dietary pattern of rachitic children at selected geographical area - Yasmin, Nahid; Ahmad, SK Akhtar; Sayed, MH Salimullah; Khan, Manzurul Haque; Karim, Md Nazmul (Bangladesh Medical Journal, 2016)
Rickets causes bone deformities through the impaired mineralization of actively growing bone affecting young children in developing countries and frequently found in Africa, Asia and Middle Eastern countries. This cross sectional study was conducted with a view to assess the dietary pattern among the rachitic children among the 151 subjects of 3 north-eastern districts of Bangladesh. Out of 151 subjects 52 were having at least one visible sign of rickets and considered as rickets case. Rest of the subjects was from their neighborhoods with no such symptoms or sign. More than half of the rachitic children were aged between 6 to 15 years, with a mean of 8.61+4.07 years. Almost all of the respondents were from low family income group. Subjects were primarily children of parents with low level of education. Most frequent complaints of the patients were bending of leg and leg pain. Average intake of calcium containing food in rachitic children was lower than normal subjects and the difference was statistically significant (p<0.05). The commonest food intake other than rice in last seven days was chapatti, which contains phytate & it is a known antagonist of calcium. Average protein intake is also found lower in the rickets patients than normal group. Insufficiency of dietary calcium is thought to be the underlying cause. Bangladesh Med J. 2014 Sep; 43 (3): 151-156